Meta-analysis of controlled studies on minimally interrupted vs. continuous use of non-vitamin K antagonist oral anticoagulants in catheter ablation for atrial fibrillation. Issue 12 (1st August 2021) - van Vugt, Stijn P G; Westra, Sjoerd W; Volleberg, Rick H J A; Hannink, Gerjon; Nakamura, Rena; de Asmundis, Carlo; Chierchia, Gian-Battista; Navarese, Eliano P; Brouwer, Marc A
Abstract: Aims: At present, there are no guideline recommendations for minimally interrupted use of non-vitamin K antagonist oral anticoagulants (mi-NOAC) during catheter ablation (CA) for atrial fibrillation (AF). Current evidence is predominantly based on observational studies, with continuous use of vitamin K antagonist in the control arm. This quantitative summary reflects the first high-level evidence on contemporary regimens, with continuous NOAC use (c-NOAC) as the current gold standard. Methods and results: Meta-analysis (Pubmed, Embase, and Web of Science) on prospective, controlled studies comparing contemporary mi-NOAC (without bridging) with c-NOAC. Net adverse clinical events (major bleeding, thrombo-embolic events) were the primary outcome. In addition, we analysed total bleeding, minor bleeding, and silent cerebral embolism. Eight studies (six randomized, two observational) with 2168 patients were summarized. The primary endpoint occurred in 1.0% (18/1835): 1.1% (11/1005) vs. 0.8% (7/830) for the mi-NOAC and c-NOAC groups, respectively; odds ratio (OR) 1.20 [95% confidence interval (CI) 0.49–2.92, P = 0.64]. The OR for total bleeding on mi-NOAC was 1.26 (95% CI 0.97–1.63, P = 0.07). ORs for minor bleeding and silent cerebral embolism were 1.17 (95% CI 0.80–1.70, P = 0.34) and 2.62 (95% CI 0.54–12.61, P = 0.12), respectively. Conclusion: This synopsis provides a quantitative synthesis of high-level evidence on a contemporary strategy of mi-NOAC in CA for AF, and overall clinical outcomes were not different from continuous NOAC use. Despite preprocedural interruption, there was no sign of lower bleeding rates. Additional higher volume datasets are warranted for more precise treatment effect estimations of this everyday alternative anticoagulation strategy in AF ablation.